Changes across Cohorts in Wage Returns to Schooling and Early Work Experiences - Jared Ashworth; V. Joseph Hotz; Arnaud Maurel; Tyler Ransom (Institute of Labor Economics (IZA), 2017)
This paper investigates the wage returns to schooling and actual early work experiences, and how these returns have changed over the past twenty years. Using the NLSY surveys, we develop and estimate a dynamic model of the joint schooling and work decisions that young men make in early adulthood, and quantify how they affect wages using a generalized Mincerian specification. Our results highlight the need to account for dynamic selection and changes in composition when analyzing changes in wage returns. In particular, we find that ignoring the selectivity of accumulated work experiences results in overstatement of the returns to education.
Keywords: C33; J22; J24; I21; I26; 330; schooling; human capital; wage returns; selection